Who Is Nostalgic About the Soviet Past? The Impact of Economic Status, Social Networks and Ideological Beliefs on the Soviet – Anti-Soviet Cleavage in Lithuania - Ramonaitė, Ainė (Sociologija. Mintis ir veiksmas, 2013)
While more than 20 years have passed from the collapse of the Soviet regime, the Lithuanian society is still deeply divided by different attitudes towards the life in the former regime. The soviet – anti-soviet attitudes allow predicting voting behavior of the Lithuanian electorate far better than any other socioeconomic or attitudinal factor. The goal of the article is to explore the determinants of the attitudes toward the soviet past of the Lithuanian citizens. The article tests the hypotheses based on the theory of political cleavages using the data of the 2012 post-electoral survey. The results of the logistic regression demonstrate that the attitudes towards the soviet past are explained by the change of social status rather than current economic position of inhabitants. Moreover, personal social networks and the experience of political mobilization in the late 1980-ies are much better predictors of the anti-soviet attitudes than socioeconomic factors. Finally, ideological beliefs appeared to have independent impact on the anti-soviet stance.